(3JNejS ddefaQLIs - (3CHh GdYHGS Hf NVQs; (3CHh GdMSf Ydj Hf Ndjd GdeUQj GdRGgO,J (B930 (3g` s ((3eOjfI ZQfGWI s)
(3ChdgG (B:s
(3ai dWa Gddg dfG Ced dGjQfi eWdHg gLd hdcd eMGhdI CLd hahGFO ehdGfG Led dTQhM GdCfaS hGdegL s
(3BNQgG (B:s
(3hef GdYfGjI HefTFI eG Od Ydi NdhU fjJg hUdGM WhjJg ced Pdc hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG hehdGfG eMeO hBdg hUMHg hSde JSdjekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs